Competition: its nature and characteristics under globalization - Маслак, Ольга Іванівна; Квятковська, Любов Абрамівна; Кулінічев, Петро Костянтинович (Technology audit and production reserves, 2014)
This paper analyzed the theoretical sources for determining the essence of the concepts of “competition” and “competitiveness”. The role of competition as a regulator of production rates and volumes, as a motivating factor for enterprises to introduce scientific and technological achievements, increase productivity, improve technology, work management etc, was justified. It was found that economic globalization requires the coordination of actions from countries worldwide for preventing the spread of crisis phenomena and for the development of agreed-upon rules of conduct in the global environment. The need to improve domestic production competitiveness could be possible now in equal opportunity conditions for competition with foreign manufacturers primarily in the domestic market, that in future should generate a sufficient level of the country competitiveness as a whole, was proved.